2021
DOI: 10.1007/978-981-16-0550-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Modeling and Stability Analysis of Piezoelectric Energy Harvesting Mechanism Under Aeroelastic Vibration

Abstract: The present research work is focused on the mechanism of harvesting electrical energy from the oscillation of the bluff body placed in airflow. A rectangular bluff body is attached to the tip of a cantilever beam which has a portion embedded with piezoelectric layers. A geometrically nonlinear distributed parameter model is derived using extended Hamilton's principle for both parallel and series connections of piezoelectric patches and solved using Newmark-beta method. Polynomial representation of aerodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A theoretical study was carried to estimate the effects of electrical load resistance on the power output (Vicente-Ludlam et al, 2014) and they found the optimal electrical resistance load that maximizes the power output for each flow velocity. A recent study (Dash et al, 2020, 2022), the effects of different order representations of the aerodynamic force on the behavior of GPEH system is investigated. A finite element model is proposed to investigate the dynamic characteristics of the GPEH system (Dash et al, 2021a, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical study was carried to estimate the effects of electrical load resistance on the power output (Vicente-Ludlam et al, 2014) and they found the optimal electrical resistance load that maximizes the power output for each flow velocity. A recent study (Dash et al, 2020, 2022), the effects of different order representations of the aerodynamic force on the behavior of GPEH system is investigated. A finite element model is proposed to investigate the dynamic characteristics of the GPEH system (Dash et al, 2021a, 2021b).…”
Section: Introductionmentioning
confidence: 99%